The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/pits.20467
|View full text |Cite
|
Sign up to set email alerts
|

School psychologists' perceptions regarding the practice of identifying reading disabilities: Cognitive assessment and response to intervention considerations

Abstract: This study surveyed a national sample of school psychologists with respect to the identification of reading disabilities (RD). It covers school psychologists' opinions regarding perceived benefits of the use of cognitive assessment in RD identification, both within and outside of an IQ -achievement discrepancy model. The survey also solicited opinions about the nature of RD, particularly conceptions of general slow learners (and readers) versus those evidencing a discrepancy. Results related to school psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…He or she has to acknowledge the existing beliefs and practices in the school; show a coherent picture of a valuable RTI model; clarify possible role changes (see below); and discuss stakeholders' perception of costs and benefits of inclusion (Denton, Vaughn, and Fletcher 2003;Le Fevre and Richardson 2002). The following important information may reduce resistance to change: School staff already working in inclusion and RTI see significantly fewer problems in implementation than staff who have not yet started (Avramidis and Norwich 2002;Machek and Nelson 2010). School staff should form several specific service teams (e.g.…”
Section: European Journal Of Special Needs Education 261mentioning
confidence: 94%
“…He or she has to acknowledge the existing beliefs and practices in the school; show a coherent picture of a valuable RTI model; clarify possible role changes (see below); and discuss stakeholders' perception of costs and benefits of inclusion (Denton, Vaughn, and Fletcher 2003;Le Fevre and Richardson 2002). The following important information may reduce resistance to change: School staff already working in inclusion and RTI see significantly fewer problems in implementation than staff who have not yet started (Avramidis and Norwich 2002;Machek and Nelson 2010). School staff should form several specific service teams (e.g.…”
Section: European Journal Of Special Needs Education 261mentioning
confidence: 94%
“…Similar to the empirical approaches of Naglieri (2011) and Flanagan and colleagues (2002;Flanagan, Ortiz, & Alfonso, 2007Flanagan et al, 2013, Hale and Fiorello (2004) provide an empirically sound approach for identifying children with SLD and other disorders entitled the Concordance-Discordance Model (C-DM) of SLD identification. In the Hale (2006) model, children who do not respond to interventions should be given a comprehensive evaluation in all areas of suspected disability, consistent with expert consensus , school psychology practitioners (Machek & Nelson, 2010), and U.S. Supreme Court decisions (Dixon, Eusebio, Turton, Wright, & Hale, 2011).…”
Section: Cognitive Assessment For Measuring Processing Strengths Andmentioning
confidence: 90%
“…Treatment acceptability has been considered to be essential for the success of a given treatment because it can predict treatment integrity, effectiveness, maintenance, and future use (Elliott 1988). Several studies have been conducted to assess levels of acceptability among school psychologists regarding different educational practices (Chafouleas, Riley-Tillman, and Eckert 2003;Machek and Nelson 2010;O'Donnell andMiller 2011). O'Donnell andMiller (2011) found that greater exposure to RtI was associated with higher acceptability ratings for RtI, as well as lower ratings for the IQ-achievement discrepancy model.…”
Section: Staff Buy-inmentioning
confidence: 98%